2022
DOI: 10.1093/geronb/gbac056
|View full text |Cite
|
Sign up to set email alerts
|

The Negative Impact of Adult Children’s Marital Dissolution on Older Parents’ Mental Health in South Korea

Abstract: Objective Little is known about whether and the extent children’s marital dissolution deteriorates older parents’ mental health. This study examines the association of children’s marital dissolution with parents’ mental health, and whether children’s gender and intergenerational contact and support moderate such an association in South Korea, where family lives are strongly linked under the Confucian collectivistic legacy. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 40 publications
3
8
0
Order By: Relevance
“…In line with recent longitudinal studies on the mental effects of children's divorce (e.g., Kalmijn & de Graaf, 2012;Ko & Sung, 2022;Tosi & Albertini, 2019), we found that a child's union dissolution is generally associated with increased parental depression, frailty, and grip strength weakness. These results lend support to our first hypothesis (Hypothesis 1).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In line with recent longitudinal studies on the mental effects of children's divorce (e.g., Kalmijn & de Graaf, 2012;Ko & Sung, 2022;Tosi & Albertini, 2019), we found that a child's union dissolution is generally associated with increased parental depression, frailty, and grip strength weakness. These results lend support to our first hypothesis (Hypothesis 1).…”
Section: Discussionsupporting
confidence: 90%
“…Longitudinal studies have provided empirical evidence for a stronger effect of children's union dissolution on mothers' mental well-being (Kalmijn & de Graaf, 2012), though other studies did not find such a gender differential effect (Ko & Sung, 2022;Milkie et al, 2008;Tosi & Albertini, 2019). Research findings are mixed also regarding children's gender.…”
Section: The Role Of Gender In the Associations Between Children's Un...mentioning
confidence: 98%
See 3 more Smart Citations